1991
DOI: 10.1021/bi00227a004
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of lysine at position 104 or 240 of TEM-1pTZ18R .beta.-lactamase enhances the effect of serine-164 substitution on hydrolysis or affinity for cephalosporins and the monobactam aztreonam

Abstract: By site-directed mutagenesis, TEM-1 beta-lactamase was altered to contain single amino acid changes of E104K, R164S, and E240K, in addition to double changes of E104K/R164S or R164S/E240K and the triple change of E104K/R164S/E240K. Hydrolysis rates for cephaloridine and benzylpenicillin were lowered at least 1 order of magnitude for all enzymes containing R164S substitutions. All mutant enzymes exhibited increased kcat values for beta-lactam antibiotics containing an aminothiazole oxime side chain. Hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
98
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 38 publications
10
98
1
Order By: Relevance
“…In general, our results with the mutations Lys-104, Ser-164, and Lys-240 are in accordance with those reported previously (28,30). Sowek et al (30) found a catalytic efficiency for cephaloridine in the Ser-164 mutant that was higher than ours, which can be related to the differences in the studied wild-type bla gene and/or in the enzyme preparation.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In general, our results with the mutations Lys-104, Ser-164, and Lys-240 are in accordance with those reported previously (28,30). Sowek et al (30) found a catalytic efficiency for cephaloridine in the Ser-164 mutant that was higher than ours, which can be related to the differences in the studied wild-type bla gene and/or in the enzyme preparation.…”
Section: Discussionsupporting
confidence: 93%
“…Sowek et al (30) found a catalytic efficiency for cephaloridine in the Ser-164 mutant that was higher than ours, which can be related to the differences in the studied wild-type bla gene and/or in the enzyme preparation. These three mutations, particularly Lys-104 and Ser-164, are in fact more frequently found among the more active extended-spectrum ␤-lactamases.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations